EFEKTIVITAS PEMBELAJARAN KOOPERATIF TIPE NHT (NUMBERED HEADS TOGETHER) DENGAN MEDIA VISUAL TERHADAP HASIL BELAJAR SISWA PADAMATERI ORGANISASI KEHIDUPAN DI KELAS VII SMP REHOBOTH - Marti, Marti; Syamswisna, Syamswisna; Ganda Putri Panjaitan, Ruqiah (Jurnal Pendidikan Matematika dan IPA, 2014)
This research is aimed to determine the effectivity of cooperative learning model through Numbered Heads Together (NHT) by visual media on students’ achievement in material life organization of VII grade SMP Rehoboth. The research is quasi experimental design, with nonequivalen control group design. The research samples are VIIa and VIIb grade. The technique of data collecting is by using random sampling. The average score of the students’ achievement that has been teach by using Numbered Heads Together (NHT) of cooperative learning model with visual media is 14,89 as higher than the conventional model of 11,29. The t-test in standard 5%  shows tcount= 5,023 bigger than its comparation to ttable = 1,679, it means there is a significant difference in the post-test result.  The counting of effect size is 1,27 it includes high, so the concluded that Numbered Heads Together (NHT) of cooperative learning model with visual media gave 39,80% of contribution on students’ achievement.Key words : Numbered heads together, visual media.